KNOWLEDGE-BASED ECONOMY AS HUMAN CAPITAL INVESTMENT TO DRIVE THE NATION'S ECONOMIC GROWTH - Rohimah, Rohimah (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Universitas Islam As-Syafi'iyah, 2021)
It is hoped that Indonesia will focus on building the quality of human resources that are adequate to increase national competitiveness. This is the the key to winning free trade and world globalization. Therefore, policies to increase knowledge and insvestment in human capital as the basis for economic improvement to improve the quality of human resources are considered to be the most effective investment that the state must make to promote long-term, inclusive economic growth. Educational growth affects economic growth and vice versa. The Role of higher education has the opportunity to improve the nation‟s economy. Learning from several developed countries, the Indonesian government must take strategic steps in an effort to build national education. Invesrments in education will significantly encourage economic progress and create social welfare. The aim of this research is to improve the quality of human capital as a capital for Indonesia‟s economic development and national assets. This theoretical study uses the literature review method. The results of the study are then presented to answer the formulation of research problems , namely 1)Knowledge_Based Economy,2)Human Capital Investment,3)Human Development Index, 4)How is The Relationshhip between Education and Economic Growth?